(untitled) (Agricultural Engineering, 2021)
The article presents the issues of water saving, declining freshwater resources in the world, and the problems of drought in the context of proper and effective irrigation of various types of crops. The use of microprocessor irrigation management systems has a significant impact on the quality of the yield and the rational use of water. An example of the irrigation system construction scheme is presented. The system uses strain gauge soil moisture sensors, which can be used to determine the relative water demand of plants, depending on the growing substrate. Additional system security in the form of rainfall and wind speed sensors provide the necessary information for the correct operation of the irrigation system. Then, two universal algorithms were proposed to automate the irrigation process of plant crops due to the way water is supplied to the plants. The first algorithm is designed for systems using drip lines - they are widely used in various types of crops where there is a need to precisely supply water to the plant, such systems are destined especially for crops grown undercover or for nursery crops. The second algorithm for sprinkler-based systems is mainly used in field crops and in mushroom farms. The presented algorithms can be used to design and implement intelligent irrigation systems, and after adding an additional module – for plant fertilization.